Peruvian Physician's Reality, Eight Years After the Initiation of Health and Social Security Reforms - Lip, César (2000)
We discuss the current reality of peruvian physicians considering a number of variables, mainly the Reform in which our Health Sector is involved and the seculary trends in the training, qualifying and performance of physicians. This is a first step in order lo make an outline of the work that our physicians are performing.